Analysis of Improving Organizational Culture Through Employee Engagement, Talent Management, Training and Development Human Resources - Febrian, Wenny Desty; Solihin, Agung (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The article analysis of improving organizational culture through employee engagement, talent management, training and human resource development is a scientific literature review article within the scope of human resource management science. The purpose of this writing is to build a hypothesis of influence between variables which can later be used for further research within the scope of human resource management science. The research method used is descriptive qualitative. Data was obtained from previous studies relevant to this research and sourced from academic online media such as publish or perish, google scholar, garba digital reference and jurnal sinta. The tool used to cite reference sources is Mendeley References. The result of this article is: 1) Employee engagement influence improving organizational culture; 2) Talent management influence improving organizational culture; and 3) Training and development of human resources influence improving organizational culture.